PENGARUH GOOD CORPORATE GOVERNANCE INDEKS DAN FINANCIAL DISTRESS TERHADAP KINERJA PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BEI PERIODE 2009-2012) - Metri Dwi Hepsari; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine the effect of good corporate governance and the influence of financial distress index on the performance of companies in the manufacturing companies listed on the Stock Exchange. The population in this study are manufacturing companies listed on the Stock Exchange in the period 2009-2012 amounted to 140 companies. The company manufactures a sample of 35 companies. Analysis of research on the use is to use multiple linear regression equation with SPSS (Statistical Product and Service Solutions). Based on t test showed that partial no significant difference between the financial distress of the Company's Performance in Manufacturing company. Based on t test showed that partially a significant difference between GCG on Firm Performance in Manufacturing company. Based on the coefficient of determination (R 2) for 0193.This suggests that financial distress and corporate governance at 19:30% effect on the Company's PerformanceKeywords: Financial Distress, GCG and Company Performance.